Pengaruh Profitabilitas, Ukuran Perusahaan, Likuiditas, dan Komisaris Independen Terhadap Nilai Perusahaan - Grandis, Bunga Silvia; Sulistyowati, Sri (Politeknik Raflesia Press, 2025)
Abstrak- This study aims to determine the effect of independent commissioners, size, liquidity, and profitability on company value in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Financial reports and company annual reports are used as secondary data in this study. Quantitative methods used. Purposive sampling method is used to select samples. The sample selection criteria are companies that generate profits during the observation period, provide complete financial reports in the country's currency, and have complete data on all research variables. Various information can be obtained from relevant companies and the Indonesia Stock Exchange (www.idx.co.id).. The results of the analysis show that profitability affects firm value positively and significantly, indicating that good financial performance benefits investors. However, firm size, independent commissioners, and liquidity have a negative impact. Large companies are not always efficient due to potential problems and operational complexity. The firm value is not always increased by the number of independent commissioners, but a high amount of liquidity may indicate that management is too conservative in implementing current activities. It is expected that this study will complement previous studies on factors that affect firm value.